Examining Racial Disparities in Colorectal Cancer Screening and the Role of Online Medical Record Use: Findings From a Cross-Sectional Study of a National Survey - Aldenise P Ewing; Fode Tounkara; Daniel Marshall; Abhishek V Henry; Mahmoud Abdel-Rasoul; Skylar McElwain; Justice Clark; Jennifer L Hefner; Portia J Zaire; Timiya S Nolan; Willi L Tarver; Chyke A Doubeni (JMIR Cancer)
Abstract BackgroundColorectal cancer (CRC) is the second leading cause of cancer-related deaths in the United States. Early detection via routine CRC screening can significantly lower risks for CRC-specific morbidity and mortality. Public health initiatives between 2000 and 2015 nearly doubled CRC screening rates for some US adults. However, screening rates remain lowest for adults aged 45‐49 years (20%), patients of safety net health care facilities (42%), adults without insurance (44%), and other subgroups compared with national averages (72%). Given the evolving landscape of digital health care and trends in web-based health information–seeking behaviors, leveraging online medical record (OMR) systems may be an underutilized resource to promote CRC screening utilization. Recognizing trends in OMR usage and patient demographics may enhance digital inclusion—a key social determinant of health—and support equitable web-based interventions aimed at boosting CRC screening across diverse populations. ObjectiveThis study examined the association of accessing an OMR with CRC screening utilization and corresponding sociodemographic characteristics of US adults. MethodsIn 2023, we conducted a secondary data analysis using a pooled, weighted sample from Health Information National Trends Survey (HINTS) 5 cycles, 2, 3, and 4 (2018‐2020), a nationally representative survey assessing how US adults access and use health-related information. We analyzed the association between sociodemographic characteristics, medical conditions, OMR access, and CRC screening behaviors via logistic regression. ResultsThe sample included adults aged 45‐75 years (N=5143). The mean age was 59 (SD 8) years for those who reported CRC screening and 52 (SD 6) years for those never screened. Nearly 70% (4029/5143) of participants reported CRC screening and 52% (2707/5143) reported OMR access in the past year. Adjusted odds of CRC screening were higher among non-Hispanic African American or Black adults than among non-Hispanic White adults (odds ratio [OR] 1.76, 95% CI 1.22‐2.53), adults who accessed an OMR (OR 1.89, 95% CI 1.45‐2.46), older individuals (OR 1.18, 95% CI 1.16‐1.21), the insured (OR 3.69, 95% CI 2.34‐5.82), and those with a professional or graduate degree versus those with a high school diploma or less (OR 2.65, 95% CI 1.28‐5.47). Individuals aged 65‐75 years were significantly more likely (P ConclusionsPromoting OMR access, especially among the most disadvantaged Americans, may assist in reaching national screening goals. Emphasis should be placed on the mutability of OMR use compared with most other statistically significant associations with CRC screening behaviors. OMR access provides an intervenable means of promoting CRC education and screening, especially among those facing structural barriers to cancer diagnoses and care. Future research should focus on tailored and accessible interventions that expand OMR access, particularly for younger populations.